2020
DOI: 10.1111/cdev.13443
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Through Collaboration: Flexibility and Diversity in Caregiver–Child Interaction Across Cultures

Abstract: Teaching supports the high‐fidelity transmission of knowledge and skills. This study examined similarities and differences in caregiver teaching practices in the United States and Vanuatu (N = 125 caregiver and 3‐ to 8‐year‐old child pairs) during a collaborative problem‐solving task. Caregivers used diverse verbal and nonverbal teaching practices and adjusted their behaviors in response to task difficulty and child age in both populations. U.S. caregivers used practices consistent with a direct active teachin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 71 publications
4
6
0
Order By: Relevance
“…Older children likely had a higher level of self-confidence as the task was easier for them than for younger children. Indeed, a recent study has shown that ni-Vanuatu children complete tasks they can do, and observe tasks they cannot do (Clegg et al, 2020), which fits the interpretation that older children decide on their own while younger children conform.…”
Section: Discussionsupporting
confidence: 60%
“…Older children likely had a higher level of self-confidence as the task was easier for them than for younger children. Indeed, a recent study has shown that ni-Vanuatu children complete tasks they can do, and observe tasks they cannot do (Clegg et al, 2020), which fits the interpretation that older children decide on their own while younger children conform.…”
Section: Discussionsupporting
confidence: 60%
“…Further evidence for this can be illustrated by additional research comparing Ni-Vanuatu and U.S. children's learning environments. When working together with children to complete a puzzle, Ni-Vanuatu caregivers used practices consistent with expectations that children learn using observation whereas their U.S. counterparts engaged in high levels of scaffolding and direct instruction (Clegg et al, 2021; as a note, these findings are consistent with Chavajay & Rogoff [2002] and Hewlett, Fouts, Boyette, & Hewlett [2011] among others). These different teaching norms may coincide with children's tendency to use the conventional or instrumental lenses more readily in different cultures.…”
Section: Introductionsupporting
confidence: 66%
“…When Western adults consider the word "teaching," they may be imagining a formal school setting in which an adult is explicitly and verbally instructing a class of same-aged children. This scenario is actually a less common and more evolutionarily novel form of teaching which does not occur with the same regularity in non-WEIRD societies (e.g., Clegg et al, 2021;Lancy, 2010;Little et al, 2016;Rogoff et al, 2015). For instance, Marshall (1958) notes that there is no formal instruction among !Kung hunter-gatherers; rather, most children learn through observing those who are more experienced.…”
Section: Cognitive Deprivationmentioning
confidence: 99%